2015
DOI: 10.1111/apm.12463
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level resistance and clonal diversity of Pseudomonas aeruginosa among chronically colonized cystic fibrosis patients

Abstract: A prospective study was conducted in Brazil to evaluate antimicrobial resistance patterns and molecular epidemiology of Pseudomonas aeruginosa isolates from cystic fibrosis (CF) patients with chronic lung infection. All isolates were obtained between May 2009 and June 2010 from 75 patients seen in four reference centers in Brazil: HCPA (20 patients) and HEOM (15 patients), located in southern and northeastern Brazil, respectively; IFF (20 patients) and HUPE (20 patients), both in southwestern Brazil. Antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In this study, we examined antibiotic susceptibility within a collection of P. aeruginosa isolates from CF patients in three northern European countries collected during routine examination, which provides a broader view than the majority of previous surveys, which have focused on a single country (18)(19)(20) or a single center (21)(22)(23). A key observation is that resistance rates were high in this population, confirming previous studies with CF patients (2), and notably much higher than that which has been reported for isolates collected in northern Europe from intensive care units (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examined antibiotic susceptibility within a collection of P. aeruginosa isolates from CF patients in three northern European countries collected during routine examination, which provides a broader view than the majority of previous surveys, which have focused on a single country (18)(19)(20) or a single center (21)(22)(23). A key observation is that resistance rates were high in this population, confirming previous studies with CF patients (2), and notably much higher than that which has been reported for isolates collected in northern Europe from intensive care units (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The first of these studies was performed in Australia and examined successively a collection of 662 carbapenem-resistant isolates assembled in 2007 to 2009 from diverse CF centers and of 517 isolates collected in a single CF center in 2011 (32). The second study was performed in Brazil and analyzed isolates from 75 patients collected from 2010 to 2011 (19). In contrast, carbapenemases have been detected in 63 out of 217 P. aeruginosa isolates collected from CF patients in China (22).…”
Section: Discussionmentioning
confidence: 99%
“…CF patients with ΔF508-CFTR mutation experience chronic Pa infections, an important cause of morbidity/mortality in these patients [ 13 ]. Based on the known autophagy inducing properties of cysteamine, we postulated that PAMAM-DEN CYS would not only function to restore ΔF508-CFTR to the cell membrane, but also decrease Pa infection and thus diminish bacterial virulence in CF airway epithelial cells by autophagy mediated bacterial clearance, in addition to its other anti-microbial effects.…”
Section: Resultsmentioning
confidence: 99%
“…The cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride channel found on epithelial cell membranes [ 1 10 ], and its dysfunction is associated with cystic fibrosis (CF) that involves dysregulation of epithelial fluid transport in the lungs, pancreas, and other organs of the body [ 7 , 8 , 11 , 12 ]. Mutations in the Cftr gene (most common being the ΔF508) is characterized by build-up of thick mucus, frequent respiratory infections (such as Pseudomonas aeruginosa , Pa ) and inflammation leading to severe lung damage [ 7 9 , 13 17 ]. These pathological manifestations caused by dysfunctional CFTR potentially involve autophagy-impairment as an important cellular mechanism associated with pathogenesis of CF lung disease [ 8 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation